Organization of primary prevention of infections sexually transmitted among orphans and children without parental care in the conditions of children's social institutions - K. I. Nikolaeva; M. A. Ufimceva; T. A. Syrneva (State Scientific Center of Dermatovenereology and Cosmetology, 2017)
The article presents the results of a survey held among orphaned children and children without parental care with regard to the prevention of sexually transmitted infections as well as results showing the efficacy of awareness-raising workshops regarding reproductive health.